VD_FINDINFO PPD - 2/13 - 21/2013 vom 30. Juli 2013 - VD Tribunal cantonal (2013)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 15 al. 2 LPP, 73 al. 2 LPP, 7 OLP, 12 OPP2